Information Support of Procedural Activities to Prove Moral Damage in Pre-Trial Proceedings - Ivanov, Dmitriy; Pcholovsky, Nikolay; Makeev, Alexey; Vasyukov, Vitaliy; Skachko, Anna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This article explores the procedure for establishing the facts of moral harm resulting from criminally punishable acts during pre-trial criminal proceedings. The study employs a qualitative research method with a normative-juridical and descriptive-analytical approach, drawing upon legal documents, statutory provisions, and expert opinions to analyze how investigators and inquiry officers handle moral damage claims. Through qualitative content analysis of case files, legal frameworks, and interview data with practitioners, the study identifies procedural gaps and best practices in ensuring justice for victims. It has been demonstrated that investigators and inquiry officers must clearly explain the victim’s right to file a civil claim, take appropriate measures to secure compensation, and provide guidance on evidence collection. The article also analyzes criteria for assessing moral damage, emphasizing the importance of documenting both the psychological and emotional consequences of criminal acts. The findings affirm the necessity of mandatory documentary proof to substantiate claims of moral harm. Moreover, the proactive role of investigators in gathering and attaching supporting documents to case files is essential, as it establishes the legal basis for courts to award fair monetary compensation proportional to the moral suffering endured by victims. REFERENCES: Burdov v. the Russian Federation (No. 2) (complaint No. 33509/04): Ruling of the European Court of Human Rights, Strasbourg, January 15, 2009. (2009). In O. A. Sadovskaya, & A. I. Ryzhov (Comp.), Case law of the European Court of Human Rights in relation to Russia: Collection of selected decisions and decisions of the ECHR for Russian judges: in 2 vols. Vol. 2. Nizhny Novgorod: Komitet protiv pytok. Chechel, G. I. (2013). Preduprezhdeniye prestupleniy – osnova zashchity interesov obshchestva [Prevention of crimes is the basis of society's interests’ defense]. Society and Law. No. 3(45), 176-180. Erofeev, S. V., & Erofeeva, A. S. (2005). Meditsinskiye i yuridicheskiye aspekty problemy vozmeshcheniya moral'nogo vreda v svyazi s povrezhdeniyem zdorov'ya i prichineniyem smerti [Medical and legal aspects of the problem of compensation for moral damage in connection with damage to health and causing death]. In Yu. D. Sergeev (Ed.), Scientific works of the II All-Russian Congress (National Congress) on medical law, Moscow, Russia, April 13-15, 2005: Collection of scientific articles. Moscow: National Medical Law Association. Grinenko, A. V. (2001). Sistema printsipov ugolovnogo protsessa i yeye realizatsiya na dosudebnykh stadiyakh [The system of principles of criminal procedure and its implementation at the pre-trial stages]: Diss. ...Doct. Jurid. Sciences. Voronezh State University, Voronezh. Gritsenko, E. N. (2005). Moral'nyy vred kak posledstviye prestupleniy protiv zhizni i zdorov'ya [Moral harm as a consequence of crimes against life and health]: Abstract. Diss. ...Cand. Jurid. Sciences. People’s Friendship University of Russia, Moscow. Kanaev v. the Russian Federation (complaint No. 43726/02): Ruling of the European Court of Human Rights, Strasbourg, July 27, 2006. (2009). In O. A. Sadovskaya, & A. I. Ryzhov (Comp.), Case law of the European Court of Human Rights in relation to Russia: Collection of selected decisions and decisions of the ECHR for Russian judges: in 2 vols. Vol. 1. Nizhny Novgorod: Komitet protiv pytok. Khasanshina, R. G. (2014). Sushchnost' i znacheniye vozmeshcheniya vreda poterpevshemu pri prinyatii protsessual'nykh resheniy po ugolovnym delam [The essence and significance of compensation for harm to the victim when making procedural decisions in criminal cases]: Diss. ...Cand. Jurid. Sciences. South Ural State University, Kazan. Komarov, I. M., & Potetinov, V. A. (2016). Problemnyye aspekty kompensatsii moral'nogo vreda v poryadke reabilitatsii [Problematic issues of compensation for moral damage in the order of rehabilitation]. Criminalist's library. Scientific Journal. No. 4(27), 59-69. Kopik, M. I. (2014). Kompensatsiya moral'nogo vreda zhertvam terrorizma [Compensation for moral damage to victims of terrorism]: Diss. ...Cand. Jurid. Sciences. Volgograd State University, Volgograd. Krivoshchekov, N. V. (2008). Grazhdanskiy isk v ugolovnom sudoproizvodstve [Civil suit in criminal proceedings]: Monograph. Tyumen: Tyumen Law Institute of the Ministry of Internal Affairs of the Russian Federation. Krylov, E. N. (2016). Chto nuzhno znat' o kompensatsii moral'nogo vreda poterpevshemu [What you need to know about compensation for moral damage to the victim]. Criminal Procedure. Vol. 9, No. 141, 32-43. Kurkina, N. V. (2011). Legal basis and practical regulation of criminal procedural activities of the police for compensation of moral damage. In A. V. Grinenko (Ed.), Criminal, criminal procedural and penal enforcement legislation (current state and directions of improvement): Collection of works of participants of the All-Russian Scientific and Practical Conference, Moscow, Russia, April 13-14, 2011. Moscow: Publishing House of Moscow State University. Melnikov, V. Yu. (2014). Obespecheniye i zashchita prav cheloveka pri primenenii mer protsessual'nogo prinuzhdeniya v dosudebnom proizvodstve Rossiyskoy Federatsii [Ensuring and protecting human rights when applying procedural coercion measures in pre-trial proceedings of the Russian Federation]: Diss. Doct. Jurid. Sciences. People’s Friendship University of Russia, Moscow. Nadyseva, E. H. (2014). Ugolovno-protsessual'nyye aspekty problemy vozmeshcheniya vreda, prichinonnogo prestupleniyem [Criminal procedure aspects of the problem of compensation for criminally caused damage]. Bulletin of the Moscow State Regional University. Series: Jurisprudence. No. 4, 88-94. Nguyen, V. T., Pushkarev, V. V., Tokareva, E. V., Makeev, A. V., & Shepeleva, O. R. (2021). Compensation for damage caused by a crime in the socialist Republic of Vietnam and the Russian Federation. Journal Cita Hukum. Vol. 9, No. 2, 211-220. https://doi.org/10.15408/jch.v9i2.21738 Ostankov, S. M. (2007). Features of compensation for moral damage in criminal proceedings. In the Thematic